Actin Dynamics: From Nanoscale to Microscale - Carlsson, Anders E. (2010)
The dynamic nature of actin in cells manifests itself in many ways: Polymerization near the cell edge is balanced by depolymerization in the interior, externally induced actin polymerization is followed by depolymerization, and spontaneous oscillations of the cell periphery are frequently seen. I discuss how mathematical modeling relates quantitative measures of actin dynamics to the rates of underlying molecular level processes. The rate of actin incorporation at the leading edge of a moving cell is roughly consistent with existing theories, and the factors determining the characteristic time of actin polymerization are fairly well understood. However, our understanding of actin disassembly is limited, in particular the interplay between severing and depolymerization and the role of specific combinations of proteins in implementing disassembly events. The origins of cell-edge oscillations, and their possible relation to actin waves, are a fruitful area of future research.